2020
DOI: 10.1021/acsami.9b20147
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Engineered Squaraine Nanoprobe for NIR-II/Photoacoustic Imaging and Photothermal Therapy of Metastatic Breast Cancer

Abstract: Various squaraine dyes have been developed for biological imaging. Nevertheless, squaraine dyes with emission in the second window (NIR-II, 1000–1700 nm) have few reports largely due to the short of a simple and universal design strategy. In this contribution, molecular engineering strategy is explored to develop squaraine dyes with NIR-II emission. First, NIR-I squaraine dye SQ2 is constructed by the ethyl-grafted 1,8-naphtholactam as donor units and square acid as acceptor unit in a donor–acceptor–donor (D–A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
66
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(68 citation statements)
references
References 56 publications
1
66
0
Order By: Relevance
“…Reproduced with permission. [ 135 ] Copyright 2020, American Chemical Society. h) UV–vis–NIR absorption spectra of the SQP‐NPs (J) and SQP‐NPs (H).…”
Section: Squaraine‐based Functional Materials For Biomedical Applicatmentioning
confidence: 99%
See 1 more Smart Citation
“…Reproduced with permission. [ 135 ] Copyright 2020, American Chemical Society. h) UV–vis–NIR absorption spectra of the SQP‐NPs (J) and SQP‐NPs (H).…”
Section: Squaraine‐based Functional Materials For Biomedical Applicatmentioning
confidence: 99%
“…Figure 25a shows a scheme of photothermal therapy, in which SQ1 was injected to the tumor cell in form of nanoprobe and then generated heat when exposed to NIR light. [ 135 ] Energy gap from intramolecular charge transfer between HOMO and LUMO can lead to long‐wavelength absorption (Figure 25b). Excited molecules release heat to be stabilized and thus become heat source.…”
Section: Squaraine‐based Functional Materials For Biomedical Applicatmentioning
confidence: 99%
“…Hyperpyrexia refers to the rise of tissue temperature to 42-46°C, while irreversible PTA can lead to tissue necrosis, which is equivalent to 240 min at 43°C or 1 s at 54°C. Yao et al [26] reported leveraging Moreover, a SQ1 nanoprobe can be used for PTA of tumors. Depending on the photothermal effect of the SQ1 nanoprobe, PAI can be carried out simultaneously (Fig.…”
Section: Pttmentioning
confidence: 99%
“…PAI of fibronectin-positive MDAMB-231 tumors at 0, 1, 2, 6, 12 and 24 h postinjection of SQ1 nanoprobe or SQ1@DSPE (control) i.v[26].…”
mentioning
confidence: 99%
“…2 Recent studies, including those regarding the detection of metastatic lymph nodes, 3 tumor and vessel imaging, [4][5][6] and intraoperative guidance, 7,8 have shown that biological imaging advantages significantly improves as wavelengths increase. Thus far, quantum dots, [9][10][11] carbon nanotubes, 12,13 rare earth-doped nanoparticles, 14,15 squaraine dyes, 16,17 semiconducting polymer nanoparticles, 18 and small-molecule dyes 5,19,20 have all been actively used for NIR-II imaging. The recent rapid development of small molecule dyes, in particular, has led to the use of effective probes for NIR-II fluorescence bioimaging.…”
Section: Introductionmentioning
confidence: 99%